Atividade das equinocandinas, anfotericina B e voriconazol frente a isolados de Candida glabrata sensíveis e resistentes ao fluconazol - Mario, Débora Alves Nunes (2012)
Widespread and prolonged usage of azoles in recent years has led to the rapid development of drug resistance in Candida species. In Candida albicans, resistance to fluconazole causes cross-resistance to other antifungals and an increase in virulence, making treatment still more difficult because of the limited therapeutical options. Nonetheless, similar phenomenon has been observed for Candida glabrata, specie that has emerged as a pathogen of clinical importance. Fluconazole resistance has been clinically described in Candida glabrata isolates and it is easily induced by in vitro exposure to the drug, but little is known about its consequences. In the present study, two groups of C. glabrata isolates were evaluated. One group was composed by fluconazole-susceptible clinical isolates (FS), and the other was composed by fluconazole-resistant (FR) laboratory derivatives from the former through an in vitro method of fluconazole resistance induction, in order to compare the activitie of the three major antifungal agent classes azoles, echinocandins and poliens. Resistant derivatives showed minimal inhibitory concentrations equal or higher than 64 μg/mL. All yeasts were tested by the broth microdilution method. Based on susceptibility parameters (MIC range, MIC50, MIC90 and geometric mean), the fluconazole-susceptible C. glabrata group (FS) was susceptible to amphotericin B (MIC90 of 0.125 μg/ml). For inhibition, the fluconazole-resistant C. glabrata group (FR) required higher concentrations of amphotericin B (MIC90 of 2 μg/ml). C. glabrata FR group showed cross-resistance with voriconazole (MIC90 of 16 μg/ml). Echinocandins showed the lowest MICs against to both group, flucoanzole-susceptible and resistant. Micafungin demostrated the lowest MIC values among all antifungal agents evaluated (MIC90 of 0.008 μg/ml in FS and 0.015 μg/ml in FR). Our results showed that resistance to fluconazole affected voriconazole susceptibility but not the echinocandin susceptibility, which demonstrated excellent activitie against tested C. glabrata groups.